1994
DOI: 10.1093/ajh/7.12.1105
|View full text |Cite
|
Sign up to set email alerts
|

24-Hour Blood Pressure Profile in Addison’s Disease

Abstract: The purpose of this study was to evaluate the circadian blood pressure rhythmicity in patients with primary adrenal insufficiency. Ten newly diagnosed and untreated patients with Addison's disease, 17 addisonian patients (including the previous 10) following an adequate regimen of corticosteroid replacement therapy, and 15 healthy subjects as a control group were studied. Twenty-four-hour ambulatory blood pressure and heart rate were measured automatically every 30 min using a Takeda TM-2420 recorder. The runs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

1996
1996
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 0 publications
1
15
0
1
Order By: Relevance
“…The CTS of AI is highly abnormal, with alteration of the Φ and absence of many circadian rhythms, for example, serum glucose and insulin sensitivity (Björnsdottir et al, 2015;Meyer et al, 2012), BP (Fallo et al, 1994), H 2 O diuresis (Azerad et al, 1957), muscle strength (Reinberg et al, 1971(Reinberg et al, , 1974, sleep staging and fatigue (García-Borreguero et al, 2000;Kong et al, 1999;Langenheim et al, 2013) and certain hormones -cortisol, renin, angiotensin, aldosterone and thyroid stimulating hormone in serum and 17-hydroxycorticosteroid (17-OHCS) and 17-ketosteroid (17-KS) metabolites in urine, plus urinary K + and Na + (Azerad et al, 1957;Björnsdottir et al, 2015;Chan & Debono, 2010;Cugini et al, 1993;Reinberg et al, 1971Reinberg et al, , 1974Samuels, 2000).…”
Section: Adrenocortical Insufficiencymentioning
confidence: 99%
“…The CTS of AI is highly abnormal, with alteration of the Φ and absence of many circadian rhythms, for example, serum glucose and insulin sensitivity (Björnsdottir et al, 2015;Meyer et al, 2012), BP (Fallo et al, 1994), H 2 O diuresis (Azerad et al, 1957), muscle strength (Reinberg et al, 1971(Reinberg et al, , 1974, sleep staging and fatigue (García-Borreguero et al, 2000;Kong et al, 1999;Langenheim et al, 2013) and certain hormones -cortisol, renin, angiotensin, aldosterone and thyroid stimulating hormone in serum and 17-hydroxycorticosteroid (17-OHCS) and 17-ketosteroid (17-KS) metabolites in urine, plus urinary K + and Na + (Azerad et al, 1957;Björnsdottir et al, 2015;Chan & Debono, 2010;Cugini et al, 1993;Reinberg et al, 1971Reinberg et al, , 1974Samuels, 2000).…”
Section: Adrenocortical Insufficiencymentioning
confidence: 99%
“…In addition to low blood pressure, a loss of circadian rhythm of blood pressure has also been recently described (12). To our knowledge, scanty data derived from direct measurements of cardiac function are available in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence to confirm the presence of the glucocorticoid receptor in vascular smooth muscle cells [48,49] and in the vascular endothelium [49][50][51], but little is known about its role at these sites. In vitro experiments with endothelial cell culture models have suggested that glucocorticoids regulate vascular reactivity via suppression of the production of vasodilators, such as prostacyclin and nitric oxide, but conflicting evidence exists in this regard.…”
Section: Vascular Glucocorticoid Effects and Nitric Oxidementioning
confidence: 99%